2022
DOI: 10.3389/fonc.2022.1038121
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1, a novel transcriptional downstream target of CD44, linking its deacetylase activity to tumor cell invasion/metastasis

Abstract: Our tetracycline-off-inducible CD44 expression system previously established in mouse model, revealed that activation of CD44 with its major ligand hyaluronan (HA) promoted breast cancer (BC) metastasis to the liver. To identify the mechanisms that underpin CD44-promoted BC cell invasion, microarray gene expression profiling using RNA samples from (Tet)-Off-regulated expression system of CD44s in MCF7 cells, revealed a set of upregulated genes including, nuclear sirtuin-1 (SIRT1 also known as NAD-dependent dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…These findings suggest that CD44 and/or CARM1 may be required for increases in SIRT1 and SIRT6 levels. Although a recent review proposes that CD44 may upregulate the SIRT1 levels via PI3K/Akt pathway, they do not provide direct evidence for CD44-mediated regulation of SIRT1 ( Ahmad et al, 2022 ). In this context, it is worth noting that PI3K-Akt-GSK3β signaling pathway is required for SIRT1 induction by ER stress ( Koga et al, 2015 ) and HMW-HA-CD44 interaction has been shown to promote proliferation of decidual cells during the early stages of pregnancy by activating the PI3K/Akt ( Zhu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that CD44 and/or CARM1 may be required for increases in SIRT1 and SIRT6 levels. Although a recent review proposes that CD44 may upregulate the SIRT1 levels via PI3K/Akt pathway, they do not provide direct evidence for CD44-mediated regulation of SIRT1 ( Ahmad et al, 2022 ). In this context, it is worth noting that PI3K-Akt-GSK3β signaling pathway is required for SIRT1 induction by ER stress ( Koga et al, 2015 ) and HMW-HA-CD44 interaction has been shown to promote proliferation of decidual cells during the early stages of pregnancy by activating the PI3K/Akt ( Zhu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%